A new model for the formation of microbial polygons in a coastal sabkha setting. (28th August 2017) - Lokier, Stephen W.; Andrade, Luiza L.; Court, Wesley M.; Dutton, Kirsten E.; Head, Ian M.; van der Land, Cees; Paul, Andreas; Sherry, Angela
Abstract: The stratigraphic record of microbially induced sedimentary structures spans most of the depositional record. Today, microbes continue to generate, bind and modify sediments in a vast range of depositional environments. One of the most cited of these settings is the coastal microbial mat system of the Persian/Arabian Gulf. In this setting, an extensive zone of microbial mat polygons has previously been interpreted as resulting from desiccation‐related contraction during episodic drying. This study employs 15 years of field‐based monitoring of the interaction between environmental factors and the development and evolution of polygon morphologies to test the desiccation model in this setting. On the basis of these observations, a new model is proposed that accounts for the genesis and development of microbial polygons without the need for desiccation‐induced shrinkage. Conversely, the formation, development and erosion of microbial polygons is a direct result of the production of large amounts of organic matter in a healthy, yet spatially limited, microbial community. The recognition of microbial polygons has previously been applied as a diagnostic tool for the reconstruction of ancient depositional environments. The present study calls these interpretations into doubt. It is inferred that preservation of the microbial polygons as a recognizable form would be rare. Biological degradation and compaction will reduce polygons to produce the 'wispy' laminae that are a common feature of ancient sabkha lithofacies. Abstract : The growth and shedding model explains the genesis and development of microbial polygons without the need to invoke desiccation‐induced shrinkage. Production of microbial polygons is a result of the overproduction of organic matter in a healthy, but spatially limited, microbial community. It is unlikely that these microbial polygons will be preserved into the depositional record in an easily recognizable form. However, the model for preservation may account for the ubiquitous presence of discontinuous wispy organic seams within the intertidal units of ancient sabkha‐system lithofacies.